Demographic and clinical profile of adolescents suicide attempters admitted to an emergency department during the COVID-19 pandemic – a retrospective cohort study using hospital information system - Tomaszek, Lucyna; Kurleto, Paulina; Turkanik, Edyta; Bielec, Ewa; Milaniak, Irena; Dąbrowska-Mędrzycka, Wioletta (Frontiers in Psychiatry, 2024)
Background The prevalence of suicidal attempts among adolescents during COVID-19 significantly increased compared with pre-pandemic estimates. The aim of the study was to explore the demographic and clinical profile of adolescent suicide attempters admitted to the emergency department during the COVID-19 pandemic. Material and method The retrospective analysis included, on the basis of electronic medical records in the CliniNet system, sociodemographic and clinical data of patients aged 10–18 years with a diagnosis of suicide attempt. Follow-up period: from March 20, 2020 to May 16, 2023. Results During the COVID-19 pandemic, there were 425 emergency department visits among adolescents aged 11–17 due to a suicide attempt, with the largest number in the 15–17 (69%) age range. The percentage of emergency department visits was higher among females (80%) and urban residents (75.3%). Self-poisoning was the most common cause of suicide attempts (52.4%), followed by self-harm (41.4%), hanging (3.2%) and jumping from a height (2.1%). The most common toxic substances in self-poisonings were antidepressants and antipsychotics, followed by paracetamol. About 70% of visits were associated with adolescent mental disorders, of which depressive disorder was the most common. One death per 425 visits was recorded (0.2%). Conclusions Adolescents attempting suicide during COVID-19 were most likely female, aged 15–17, city dwellers, undergoing psychiatric treatment mainly for depressive disorders. The mental health consequences of the pandemic may be more long term, and further monitoring will be needed in the years to come.